High-Quality Outdoor Learning Evidence-based Education Outside the Classroom for Children, Teachers and Society - Jucker, Rolf.; von Au, Jakob; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This open access book reviews evidence and case studies on the effects of outdoor learning on teachers and learners. It shows how real-world learning outside the classroom contributes to unlocking the full potential of learners, demonstrating its benefits for academic learning, social competencies, personal and emotional development, psychological well-being, and physical activity and health. In addition, the book highlights how outdoor learning nurtures environmental awareness and helps learners to tackle current sustainability challenges. Its focus on high-quality learning makes it a unique contribution to the implementation of SDG 4. Aimed at lecturers at teacher training universities, teachers, professional educators, coaches, and multipliers who train staff of educational NGOs, as well as decision makers on all levels of education systems, this book is of interest to all those who seek a more in-depth understanding of the future of education.
Accumulating scientific evidence that EotC is high quality learning / supporting the learning potential of kids -- Cathy Jordan and Louise Chawla: A Coordinated Research Agenda for Nature-Based Learning -- Kuo Ming, Barnes Michael, Jordan Catherine: Do Experiences With Nature Promote Learning?Converging Evidence of a Cause-and-Effect Relationship -- Kuo Ming, Browning Matthew H. E. M., Penner Milbert L.: Do Lessons in Nature Boost Subsequent Classroom Engagement? Refueling Students in Flight -- Louise Chawla: Childhood nature connection and constructive hope: A review of research on connecting with nature and coping with environmental loss.
Keywords: Outdoor education; Environmental education; Human geography; Outdoor Education; Environmental and Sustainability Education; Human Geography